2020
DOI: 10.1002/ldr.3590
|View full text |Cite
|
Sign up to set email alerts
|

Wind erosion control using inoculation of aeolian sand with cyanobacteria

Abstract: Wind erosion is a natural phenomenon that has been increasing due to anthropogenic activities. Wind erosion has detrimental consequences on the environment, and its prevention is a critical issue in many arid regions of the world. The topic of this study was an artificial formation of biocrusts to diminish wind erosion by inoculation of the aeolian sand by two filamentous cyanobacteria of Nostoc punctiforme and Microcoleus vaginatus. The erodibility of the sand was examined in a wind–tunnel equipped with a san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 28 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…The results of the penetrometer tests conducted by Fattahi et al (2020bFattahi et al ( ,c,d, 2021, Langston and McKenna-Neuman (2005), and McKenna-Neuman and Maxwell (2002) demonstrated that depending on the structure and component of the crusts, a depth of 30 grain diameters (by assuming a 200 μm-diameter saltating particle) or even more would be required to reach the ultimate strength. However, impacting particles penetrate the crust only a few grain diameters and scratch the surface (Shao, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the penetrometer tests conducted by Fattahi et al (2020bFattahi et al ( ,c,d, 2021, Langston and McKenna-Neuman (2005), and McKenna-Neuman and Maxwell (2002) demonstrated that depending on the structure and component of the crusts, a depth of 30 grain diameters (by assuming a 200 μm-diameter saltating particle) or even more would be required to reach the ultimate strength. However, impacting particles penetrate the crust only a few grain diameters and scratch the surface (Shao, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, active intervention may be required for faster re-establishment of a viable and dense biocrust cover. This was realized in studies that directly applied representative biocrust organisms to the soil surface, using cyanobacteria (Chen et al 2006;Rossi et al 2017;Fattahi et al 2020;Zhao et al 2021), bryophytes (Xiao et al 2015;Bu et al 2018;Cruz de Carvalho et al 2018), or lichens (Ballesteros et al 2017). Furthermore, the application of stabilizers (Park et al 2017;Peng et al 2017;Li et al 2021) showed accelerated development of cyanobacterial biocrusts.…”
Section: Introductionmentioning
confidence: 99%
“…Wind erosion, the movement of course and fine particles by wind, is among natural process that mostly occurs under dry conditions and high wind velocity (Mirhasani et al, 2019;Jarrah et al, 2020), and degrade more than one-third of the 'Earth's land surface (Fattahi et al, 2020). The wind erosion may be accelerated by anthropogenic pressures such as overgrazing rangelands, excessive clearances of native vegetation, deforestation, abandoning farmland, monoculture systems, over-harvesting vegetation, or leaving cultivated lands fallow for a long time (He et al, 2006;Chen et al, 2013), resulting in an increase in the rates of soil loss.…”
Section: Introductionmentioning
confidence: 99%
“…The wind erosion may be accelerated by anthropogenic pressures such as overgrazing rangelands, excessive clearances of native vegetation, deforestation, abandoning farmland, monoculture systems, over-harvesting vegetation, or leaving cultivated lands fallow for a long time (He et al, 2006;Chen et al, 2013), resulting in an increase in the rates of soil loss. Wind erosion decreases water quality and negatively impacts biodiversity and climate changes (Lal, 1994;Fattahi et al, 2020). In addition, the negative effects of wind erosion on soil nutrients have been reported; wind erosion may negatively affect nutrients such as nitrogen by blowing off the most fertile topsoil (Lei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%